Giraffes at the zoo - Ward, Finn (New York Gareth Stevens, 2016)
A book about giraffes at the zoo for beginning readers.
Zoo home -- All in the neck -- Many spots -- Time to eat -- Words to know.
Includes index.
Keywords: Giraffe; Zoo animals; Juvenile works